Signaling Centers Drive Brachyury Dynamics and Lineage Commitment in mESC Aggregates - A. Rabeling; M. Goolam (FASEB BioAdvances)
ABSTRACT Stem cell‐based models of embryogenesis have exploded in popularity, resulting in protocols with overlapping use of some reagents and differential use of others. As such, the precise contributions of individual signaling molecules, such as Chiron and BMP4, applied to whole or part of aggregates, and matrices, such as Matrigel, to the development of these models are unknown. Furthermore, the use of these different methods, signaling molecules, and matrices has yet to be directly compared under the same conditions. In this paper, we used a mouse embryonic stem cell aggregate model to compare the use of Chiron and BMP4 signaling as pulses (applied to the whole aggregate) or signaling centers (applied to part of the aggregate) and embedded them in low‐percentage Matrigel. Each factor had different effects on morphology, Brachyury protein expression, and lineage commitment, with signaling centers having different effects to pulses. BMP4 as a pulse was shown to drive neural differentiation, while signaling centers resulted in better recapitulation of aspects of anterior–posterior axis formation, with polarization of Brachyury protein and expression of anterior and posterior genes observed. This further elucidates the contributions of Chiron and BMP4 to aggregate development to better inform decisions around experimental conditions for in vitro models of embryonic development.